Pengaruh Perbandingan Tepung Beras Merah (Oryza nivara L.) dan Tepung Kecambah Kacang Merah (Phaseolus vulgaris L.) Terhadap Karakteristik Flakes - Stephanie Gloria, Jacqueline; Wisaniyasa, Ni Wayan; Yusa, Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 2 (2022): Jurnal ITEPA, 2022)
This study aimed to determine the effect of the comparison of red rice flour and red bean sprouts flour on the characteristics of flakes and find out the comparison of red rice flour and red bean sprouts flour to obtain the best characteristics of the flakes. The experimental design used was Completely Randomized Design with the comparison treatment red rice flour and red bean sprouts flour as a treatment which consist of 4 levels: 40%:60%, 50%:50%, 60%:40%, and 70%:30%. The treatment was repeated four times, resulting in 16 experimental units. The data obtained were analyzed using an analysis of variance and if the treatment had a significant effect, it was followed by a Duncan Multiple Range Test (DMRT). The result showed that the comparison of red rice flour and red bean sprouts flour had a significant effect on water content, ash content, protein content, fat content, carbohydrate content, crude fiber content, endurance time crispness in milk, color, aroma, texture, taste, and overall acceptance. The flakes produced from the comparison of 40% red rice flour and 60% red bean sprouts flour had the best characteristics, which had water content 3.13%, ash content 4.48%, protein content 17.20%, fat content 6.09%, carbohydrate content 68.75%, crude fiber content 9.36% and endurance time crispness in milk for 1 minutes 57 seconds. The flakes had a liked color, a liked and slightly red rice aroma, a liked texture and slightly crispy, a slightly liked taste, and a liked overall acceptance.